Perbedaan Tingkat Nyeri Metode Konvensional dan Eracs pada Ibu Post SC di Ruang Nifas Rsia Sitti Khadijah Kota Gorontalo - Ani Retni; Fahmi A. Lihu; Dwi Safira Putri S. Giu; Dwi Nur Octaviani Katili (Jurnal Ilmiah Kedokteran dan Kesehatan, 2025)
The pain level of Post SC patients varies, depending on the perception and pain threshold of each patient. Post SC patients will experience pain in the incision area wound because it is caused by tears in the front abdominal wall tissue. This study aims to determine the difference in pain levels between conventional methods and the ERACS (Enhanced Recovery After Cesarean Section) method in post-SC mothers in the Postpartum Room of RSIA Sitti Khadijah Gorontalo City. The design of this study was quantitative with a cross-sectional approach, involving 40 respondents selected using purposive-sampling technique. The instrument used was an observation sheet to measure pain levels using the Numeric Rating Scale (NRS). The results showed that the highest level of maternal pain post SC conventional method was moderate pain as many as 13 people (65.0%), mild pain as many as 4 people (20.0%) and the lowest was severe pain as many as 3 people (15.0%). While the highest level of maternal pain post SC Eracs method was mild pain as many as 16 people (80.0%), moderate pain was 4 people (20.0%) and there were no respondents who experienced severe pain. The P value obtained was 0.001 <0.05. In conclusion, the ERACS method is more effective in reducing pain intensity than conventional methods, allowing patients to recover faster and start early mobilization.